Processing in the quality of tanzania grass seeds - de Melo, Lilian F. [UNESP]; Martins, Cibele C. [UNESP]; da Silva, Givanildo Z. [UNESP]; Sanches, Mauricio F.G. [UNESP] (FapUNIFESP (SciELO), 2016)
The available research concerning the processing of grass seeds is scarce, despite its fundamental importance for national and international agribusiness. The objective of this project was to evaluate the effects of processing phases on the physical and physiological quality of tanzania grass seeds for commercialization purposes. Seeds were sampled before processing and after leaving the air and screen machine (upper and intermediate screens and bottom); first gravity table (drift, upper and intermediate spouts); treating machine second gravity table (upper, intermediate, and lower spouts). Seeds were evaluated as to water content, physical quality (purity and 1,000 seeds weight) and physiological (germination, first count of germination, seedling vigor rating, seedlings length of primary roots and shoots, seedling emergence in the field, and emergence speed index). The processing of Tanzania grass seeds in the air screen cleaner machine and gravity table are efficient to improve the physical quality of the lot. The seed treatment with dye ink reduces the seedlings emergence speed in the field. The processing is not required to meet the national commercialization standards of the Tanzania grass seeds, but for the international.
Keywords: Germination; Panicum maximum; Pastures; Tropical grass; Vigor